DAMPAK SPIRITUALITAS KERJA PADA KINERJA PEGAWAI DLH DOMPU MELALUI KOMITMEN ORGANISASI - Evi Evi; Mahmud Mahmud; Fahrul Mauzu (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
Employee performance in the public sector often fluctuates due to a lack of strong internal drive. This study aims to analyze the effect of Workplace Spirituality on Employee Performance through Organizational Commitment as an intervening variable at the Environmental Service (DLH) of Dompu Regency. Using a quantitative approach with an explanatory design, this study involved 53 Civil Servants (PNS) selected via purposive sampling. Data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) based on the S-O-B-C theory. The results show that Workplace Spirituality has a positive and significant effect on Employee Performance, both directly and indirectly. Specifically, spirituality has the strongest impact on forming Organizational Commitment. Commitment is proven to act as a vital mediator bridging the transformation of spiritual values where work is perceived as worship into productive work behavior. These findings confirm the "Values to Action Transformation" model, implying that integrating spiritual values and strengthening loyalty are effective strategies for improving the performance of apparatus in local government agencies.